Panji, Past, Now, and Coming: Millennial Perspective on the Benefits of Panji Lectures - I Dewa Gde Satrya (Research Collaboration Community (RCC), 2022)
The cultivation of local cultural values through the Panji course at the Tourism Studies Program, Ciputra University Surabaya, has been running since 2015 until now. This study aims to describe the millennial perspective on the benefits of Panji's course in daily life and future work. The research method is qualitatively using thematic analysis. The research results show that the informants of this study were students who took the Panji course for one semester and Panji's expert as a validator. The conclusions of this study are as firstly, Panji inspires positive values that are relevant in today's life; second, Panji is a spirit that inspires future work, both as professionals and entrepreneurs in the tourism sector. It is hoped that the Panji Millennial Perspective is useful for youth regarding the Benefits of College.